Analisis Kekasaran Permukaan Benda Kerja Hasil Pembubutan dengan Variasi Jenis Material dan Pahat Potong - Budi Istana; Sunaryo Sunaryo; jon kennedi (Jurnal Surya Teknika, 2017)
The surface shape and roughness of a product produced by machine tools such as lathe plays an important role. This is due to the surface shape and roughness of the product related to friction, wear, lubrication system and so on. The machining process will determine the surface roughness at a certain level where the surface roughness can be used as a reference for evaluation of machining products. The surface roughness of a product does not have to be of little value. One product that is required to have a low surface roughness is the shaft. In the analysis of surface roughness, the steps taken are the selection of work material and the type of chisel that is often used in production workshops in Pekanbaru. Material of the workpiece used is ST41 and S45C while the type of cutting tool used is HSS and Widia Carbide. For the next process is the process of making workpieces with lathes with variations of types of cutting tool on each material workpiece. HSS chisel and carbide with ST41 steel material with rotation variation 300 rpm, 500 rpm and 840 rpm. In this material using HSS chisel it has increased roughness from 300 rpm (3,254 μm) to 500 rpm (5,425 μm) while 840 rpm (5,212 μm) has decreased roughness. otherwise the carbide has a roughness rate of 300 rpm (4,154 μm), 500 rpm (4,035 μm) and a round of 840 rpm (2,608 μm). HSS chisel and carbide with S45C steel material with rotation variation 300 rpm, 500 rpm and 840 rpm. In this material using HSS chisel has increased roughness from 300 rpm (5,778 μm) to 500 rpm (6,563 μm) while 840 rpm (5,712 μm) decreased roughness. otherwise the carbide has a roughness rate of 300 rpm (5.050 μm), 500 rpm (4,785 μm) and 840 rpm (4,116 μm).